Rancang Bangun Sistem Informasi Pemilihan Fasilitas Kesehatan Berbasis PCA dan Fuzzy AHP - Aditya Chandra Nugraha,; I Wayan Supriana,; I Made Satria Bimantara, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
This paper discusses a proposed development process of an information system for the placement of health facilities in Bali by utilizing a fuzzy analytical hierarchy process and principal component analysis to reduce the dimensionality of the various datasets used in the decision making process. Fuzzy AHP is used to determine the weights of nine distinct criteria, including distance to population centers, service quality, infrastructure availability, population density, and healthcare accessibility, among others. Principal Component Analysis (PCA) helps in extracting the most influential variables from socio-economic, geospatial, and satellite-based datasets, simplifying the input without significant loss of information. The system is built using the Laravel framework and offers functionalities for both users seeking facility recommendations and authorities proposing new locations. Manual Fuzzy AHP calculations showed a consistency index of 0.23, indicating the need for improved consistency in pairwise comparisons. Overall, the system successfully automates the recommendation process, combining expert judgment and data-driven analysis to support equitable and effective placement of health services.
Keywords: Fuzzy AHP (FAHP); Principal Component Analysis (PCA); Geospatial Analysis